An approach towards metastatic neck nodes and most common site of primaries: a retrospective study - Prakash, Rudra; Dutta, Smrity Rupa Borah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Head and neck cancer is one of the most common cancers in India and worldwide. It accounts for 30 percent of the total cancer burden. Head and neck cancers are notorious for loco regional spread presenting late with metastastasis to cervical lymph nodes. Methods: Our study was carried out on patients presenting with metastatic neck nodes at Silchar Medical College and Hospital, Assam from 1st April 2013 to 30th March 2015. Results: In our study 167 patients presented with head and neck cancer with metastatic neck nodes. Metastatic nodes involving level II accounted for 51.4% of cases with primaries in oral cavity, base of tongue. Level III lymph nodes were involved in 48.6% of cases with primaries in the hypopharynx and larynx. Conclusions: In our study it was found that hypopharynx is the most common primary head and neck cancer with metastatic neck node. The most commonly involved lymph nodes are level II and level III. This helps in understanding the pattern of micrometastases in head and neck cancer patients with N0 neck which makes way for the role of selective neck dissection in these groups of patients.